Education On Prevention Of Pulmonary Tuberculosis Transmission Using TikTok Media - Rahayu, Eksanti Septa; Mugianti, Sri; Suprajitno, Suprajitno (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
The incidence of pulmonary tuberculosis (pulmonary TB) continues to increase every year, one of the contributing factors is the lack of public knowledge about pulmonary tuberculosis so that there are still many people who are not healthy. The purpose of this study was to describe family knowledge about preventing pulmonary tuberculosis transmission using TikTok media at the Sukorejo Health Center. This research uses a descriptive method. The population in this study were all families accompanying pulmonary tuberculosis patients who were still registered and actively seeking treatment at the Sukorejo Health Center from January to April 2023, totaling 20 people. A sample size of 20 accompanying families of pulmonary tuberculosis patients was taken using total sampling technique. Data collection used an instrument in the form of a questionnaire. The results of the study were: family knowledge about preventing the transmission of pulmonary tuberculosis using TikTok media as much as 80 Percent in the good category, 20 Percent in the enough category. Not all families can understand the prevention of pulmonary tuberculosis transmission using TikTok media, so a holistic approach is needed. Various parties need to work together to increase family understanding about preventing the transmission of pulmonary tuberculosis